11=8x+10-x+5

Simple and best practice solution for 11=8x+10-x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=8x+10-x+5 equation:


Simplifying
11 = 8x + 10 + -1x + 5

Reorder the terms:
11 = 10 + 5 + 8x + -1x

Combine like terms: 10 + 5 = 15
11 = 15 + 8x + -1x

Combine like terms: 8x + -1x = 7x
11 = 15 + 7x

Solving
11 = 15 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
11 + -7x = 15 + 7x + -7x

Combine like terms: 7x + -7x = 0
11 + -7x = 15 + 0
11 + -7x = 15

Add '-11' to each side of the equation.
11 + -11 + -7x = 15 + -11

Combine like terms: 11 + -11 = 0
0 + -7x = 15 + -11
-7x = 15 + -11

Combine like terms: 15 + -11 = 4
-7x = 4

Divide each side by '-7'.
x = -0.5714285714

Simplifying
x = -0.5714285714

See similar equations:

| 5x+2=3(2x-4)+8 | | 4b=4b+33 | | (x-1)/(4x+7)=1/5 | | 12x+-12+23=56 | | 62.9296*x+64.9278*(100-x)=63.546 | | (2x^5+5x^4+25X^3+30x^2+45x+65)=0 | | solvex^4-9x^2+8=0 | | 67=8n+5 | | Z+y/5 | | 5-2x=-13-5x | | 2/5=a-4/6 | | 6-2(x+3)-x=-x-4(x+2) | | X=5(4x) | | -(3y+2)-(-2y-3)=-5 | | -1-8p=-10p-9 | | 7/m=3/m-2 | | 9y=2y^2+4 | | X/-2-14=-10 | | 3(4m+5)=3m-3 | | 21x^2-13x=-8 | | 2(x-1)/6=3x-5 | | -3(2x-1)=11x | | 6n+4=1n-11 | | -23-11= | | -3+12=13x-5-12x | | 7/9=p+1/3 | | 54+.09m=38+.13m | | 5x/x-1+1/x=6 | | 1/6y^2=y-3/2 | | 33x^2-37x+10=0 | | 8(x+1)=16+8x | | 7n+4=-11 |

Equations solver categories